MLSD: um protocolo de divulgação de estados dos enlaces para redes em malha sem fio infraestruturadas - Porto, Daniel Charles Ferreira (2010)
The increasing popularity and demand of wireless networks, over the past few years, has led to new challenges that stimulate the development of technology to build better standards and protocols. In such a context arises the Wireless Mesh Networks (WMN) which are low cost, self-organized and self-configurable networks that are easy to deploy and are fault tolerant. The WMN are aiming to achieve better performance, greater reliability and flexibility when compared to other wireless networks. These networks can provide an infrastructure consisting of dedicated devices for routing, strategically placed to achieve adequate coverage, providing connectivity within the coverage area for mobile clients. Therefore, these networks need to adapt to topology changes that can occur at any time. To allow this adjustment a routing protocol is required. An important component of a proactive routing protocol is a network topology discovery protocol, which disseminates link-state updates messages over the network. The proactive protocols usually have a high message overhead. However, a high message overhead has a major impact on the performance of a routing protocol and can lead to scalability problems. In such a context, the main contribution of this work is to build a reliable link-state dissemination protocol, called MLSD specially designed for RMSF whose goals are to reduce the messages overhead and reduce the total messages sent to advertise topology changes.